STRATEGI DAKWAH PEJUANG SUBUH DALAM MENINGKATKAN SHALAT SUBUH BERJAMA’AH DI TEMBILAHAN KABUPATEN INDRAGIRI HILIR - Oktaria Nolanda; Junaidi (ADISAM PUBLISHER, 2023)
Subuh fighters are a missionary community formed by young people as a movement to promote congregational morning prayers at mosques and several religious activities related to the missionary movement in Tembilahan. The dawn warrior's missionary journey in society does not only focus on preaching bil-lisan and bil- kitabah, but also on the relationship and interdependence between goals that can work together with da'wah. Da'wah can even be a catalyst for social movements that have a positive influence on community activities. This research was conducted to find out how the dawn warriors' da'wah strategy was used to increase congregational morning prayers in Tembilahan, Indragiri Hilir district, as well as the supporting and inhibiting factors for the dawn warriors' da'wah strategy in increasing congregational morning prayers in Tembilahan, Indragiri Hilir district. The type of research used in this research is a type of research with a descriptive qualitative approach, the preferred data collection methods are observation, interviews, and documentation if files are needed for data collection, documentation. The results of the research can be concluded that the Tembilahan dawn warriors are seen from Fred R. right. The challenge faced is how to introduce and motivate that the morning prayer is important, an obligation for every Muslim and why Muslims must perform the morning prayer. As well as supporting and inhibiting factors, both internal (management) and external (society)